Kreativitas Juhermi Tahir dalam Tari Jepin Tali Bui Kota Pontianak - Ismunandar Ismunandar (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
Jepin Tali Bui dance in general as an art form that was inherited by the culture of the old people. The Jepin Tali Bui dance continues to develop in West Kalimantan, both from the development of movement steps, music, property accompaniment, clothing and art performers. Where in terms of motion, it does not leave the typical movement of the jepin movement, namely the number of foot movements and placing the heel at the beginning of the movement. Typical Malay music with stringed and segmented musical instruments, a very distinctive property of the tali bui jepin dance is the rope. For this reason, at this time creative people are needed who are able to develop a dance so that it does not become extinct. This has resulted in new innovations in the movement pattern of the Jepin Tali Bui dance, the technique of the Jepin Tali Bui dance, as well as the musical accompaniment of the current Jepin Tali Bui dance, especially the Jepin Tali Bui dance, the result of the creativity of Juhermi Tahir himself. The results of this study are expected to be used as a reference for further research and the Jepin Tali Bui Dance in Pontianak City can be used as an alternative as a performance medium for appreciation in the form of dance videos and recordings of Jepin Tali Bui dance music which will be used as a medium for appreciation of dance in the world of education such as schools. , study program, community.Tari Jepin Tali Bui secara umum sebagai salah satu bentuk seni yang diwariskan oleh kebudayaan orang tua dulu. Tari Jepin Tali Bui terus berkembang di Kalimantan Barat, baik dari perkembangan langkah gerak, musik, iringan properti, busana dan pelaku seninya. Dimana dari segi gerak, tidak meninggalkan gerakan khas dari gerak jepin yaitu banyaknya pergerakan kaki dan menitikan tumit di awal gerakan. Musik khas melayu dengan alat musik gambus dan beruas, properti yang sangat khas dari tari jepin tali bui adalah tali. Untuk itu, saat ini memang diperlukan orang-orang kreatif yang mampu untuk mengembang sebuah seni tari agar tidak punah. Hal tersebut telah menghasilkan inovasi baru dalam pola gerak tari Jepin Tali Bui, teknik gerak tari Jepin Tali Bui, serta iringan musik tari Jepin tali Bui saat ini saat ini, khususnya tari Jepin Tali Bui hasil dari kreativitas seorang Juhermi Tahir itu sendiri. Hasil penelitian ini diharapkan dapat dijadikan acuan bagi penelitian selanjutnya dan Tari Jepin Tali Bui di Kota Pontianak dapat dijadikan alternatif sebagai media pertunjukan untuk apresiasi yang berupa video tari dan rekaman musik tari Jepin Tali Bui yang akan dimanfaatkan sebagai media untuk apresiasi seni tari didunia pendidikan seperti sekolah, program studi, komunitas.